STOCK RETURN OF MANUFACTURING COMPANIES IN INDONESIA:INFLUENCE BUSINESS STRATEGY, EVA, MANAGERIALOWNERSHIP AND SIZE - Priyo Susilo; Abdurrosyid; Dirvi Abbas; Sasa Suratman (JRAK, 2023)
The purpose of this study is to determine the effect of business strategy, economic value added (EVA), managerial ownership and size on stock profitability in manufacturing companies in the basic industrial and chemical sectors listed on the Indonesia Stock Exchange. The population of this study includes manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2016-2020. The sampling method uses a targeted sampling method. The type of data used in this study is secondary data using panel regression data analysis method. The results showed that business strategy and management ownership had a positive impact on stock returns. however, EVA and size do not affect stock returns.